Non-invasive ventilation for SARS-CoV-2 acute respiratory failure: a subanalysis from the HOPE COVID-19 registry - Bertaina, Maurizio; Nuñez-Gil, Ivan J.; Franchin, Luca; Rozas, Inmaculada Fernández; Arroyo-Espliguero, Ramón; Viana-Llamas, María C.; Romero, Rodolfo; Eid, Charbel Maroun; Uribarri, Aitor; Becerra-Muñoz, Víctor Manuel; Huang, Jia; Alfonso, Emilio; et al. (Emergency medicine journal, 2021)
Background The COVID-19 pandemic has seriously challenged worldwide healthcare systems and limited intensive care facilities, leading to physicians considering the use of non-invasive ventilation (NIV) for managing SARS-CoV-2-related acute respiratory failure (ARF). - Methods We conducted an interim analysis of the international, multicentre HOPE COVID-19 registry including patients admitted for a confirmed or highly suspected SARS-CoV-2 infection until 18 April 2020. Those treated with NIV were considered. The primary endpoint was a composite of death or need for intubation. The components of the composite endpoint were the secondary outcomes. Unadjusted and adjusted predictors of the primary endpoint within those initially treated with NIV were investigated. - Results 1933 patients who were included in the registry during the study period had data on oxygen support type. Among them, 390 patients (20%) were treated with NIV. Compared with those receiving other non-invasive oxygen strategy, patients receiving NIV showed significantly worse clinical and laboratory signs of ARF at presentation. Of the 390 patients treated with NIV, 173 patients (44.4%) met the composite endpoint. In-hospital death was the main determinant (147, 37.7%), while 62 patients (15.9%) needed invasive ventilation. Those requiring invasive ventilation had the lowest survival rate (41.9%). After adjustment, age (adjusted OR (adj(OR)) for 5-year increase: 1.37, 95% CI 1.15 to 1.63, p<0.001), hypertension (adj(OR) 2.95, 95% CI 1.14 to 7.61, p=0.03), room air O2 saturation <92% at presentation (adj(OR) 3.05, 95% CI 1.28 to 7.28, p=0.01), lymphocytopenia (adj(OR) 3.55, 95% CI 1.16 to 10.85, p=0.03) and in-hospital use of antibiotic therapy (adj(OR) 4.91, 95% CI 1.69 to 14.26, p=0.003) were independently associated with the composite endpoint. - Conclusion NIV was used in a significant proportion of patients within our cohort, and more than half of these patients survived without the need for intubation. NIV may represent a viable strategy particularly in case of overcrowded and limited intensive care resources, but prompt identification of failure is mandatory to avoid harm. Further studies are required to better clarify our hypothesis. - Trial registration numbers NCT04334291/EUPAS34399.
Gesehen am 15.11.2021